PENGARUH REALISASI PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM DAN DANA ALOKASI KHUSUS TERHADAP TARGET PENDAPATAN DAERAH (SURVEI PADA KABUPATEN/KOTA SE-SULAWESI TENGAH) - Dewi, Gitta (Katalogis, 2013)
Abstract          This research aims to investiagte and analyse simultaneous and partial effects of regional original income realization, general allocation fund and specific allocation fund on regional income target in all regency/city ini Central Sulawesi. Sample of this research covers 10 out of 11 regencies/city in Central Sulawesi. To select those samples, this research employs purposive sampling method. This is a descriptive verificative research method using multiple linear regressions as an analysis tool. The results show that the effects of original income realization, general allocation fund and specific allocation fund on regional income target (indicated by adjusted R square) is 65.6 % and the rest i.e. 34.4 % affected by other factors. Based on simultaneous test indicates that regional original income realization, general allocation fund and specific allocation fund perfom significant effects on regional income target in all regency/city in Central Sulawesi. Partially, regional income realization does not perform significant effect on regional income target. Meanwhile, general allocation fund and specific allocation fund perform significant effects on regional income target.